Contrived publications and COVID-19 communication noise - Sorooshian, Shahryar; T., Senthil Kumar (PAGEpress, Italy, 2020)
At present, effective antivirals against the coronavirus infection disease 2019 (COVID-19) do not seem to be available, and hence medical practitioners and governments are vying for any useful information on the treatment and management of this outbreak. Research journals have played their part by promotingCOVID-19 research to ensure that the stakeholders have immediate access to adequate information.